AHMADIYAH DALAM POTRET MEDIA CETAK (Analisis Isi Berita Surat Kabar Kompas, Republika, dan Suara Pembaruan) - Andi Subhan Amir (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2013)
This study aims to: (1) identify trends in attitudes towards news content of daily newspaper of Kompas, Republika and Suara Pembaruan in presenting news of Ahmadiyah case and (2) determine the dominant news topic in the news presentation on the Ahmadiyah case of a daily newspaper of Kompas, Republika, and Suara Pembaruan. The study was carried out for about three months from September to December 2011. The object of this study was Ahmadiyah news published in the daily newspaper of Kompas, Republika, and Suara Pembaruan.The type of research is descriptive quantitative using content analysis method. Population and samples in this study were all news coverage about the Ahmadiyah case published on daily newspaper of Kompas, Republika, and Suara Pembaruan. The news were taken within period of February 6, 2011 to April 31 2011. The entire population used as samples due to limitation of population. Data collection techniques for primary data used coding sheets. Whereas for the secondary data, It was obtained from the study of literature from books or from internet sites that are relevant to the focus of the. The results showed that all three printed media (Kompas, Republika, and Suara Pembaruan) in presenting news about Ahmadiyah case, in relation to the incident of Cikeusik Ahmadiyah, tended to be neutral. The most dominant news topic in the presentation of news on the Ahmadiyah case in daily newspaper of Kompas, Republika, and Suara Pembaruan was about law. The percentage for this category by 65%, more than half of the total 210. This indicated that Kompas, Republika, and Suara Pembaruan strived to present news objectively by seeing Cikeusik riot as legal issues.